A Multifrequency Global View of Callisto’s Thermal Properties from ALMA - Maria Camarca; Katherine de Kleer; Bryan Butler; Alexander Thelen; Cole Meyer; Alex B. Akins; Imke de Pater; Mark A. Gurwell (The Planetary Science Journal)
We present thermal observations of Callisto’s leading and trailing hemispheres obtained using the Atacama Large Millimeter/submillimeter Array (ALMA) at 0.87 mm (343 GHz), 1.3 mm (233 GHz), and 3 mm (97 GHz). The angular resolution achieved for these observations ranged from $0\mathop{.}\limits^{^{′′} }09\,to\,0\mathop{.}\limits^{^{′′} }24$ , corresponding to ∼420–1100 km at Callisto. Global surface properties were derived from the observations using a thermophysical model constrained by spacecraft data. We find that Callisto’s millimeter emissivities are high, with representative values of 0.85–0.97, compared to 0.75–0.85 for Europa and Ganymede at these wavelengths. It is clear that models parameterized by a single thermal inertia are not sufficient to model Callisto’s thermal emission, and clearly deviate from the temperature distributions in the data in systematic ways. Rather, more complex models that adopt either two thermal inertia components or that treat electrical skin depth as a free parameter fit the data more accurately than single thermal inertia models. Residuals from the global best-fit models reveal thermal anomalies; in particular, brightness temperatures that are locally 3–5 K colder than surrounding terrain are associated with impact craters. We identify the Valhalla impact basin and a suite of large craters, including Lofn, as key cold anomalies (∼3–5 K) and geologic features of interest in these data. These data provide context for Callisto JWST results as well as the other ALMA Galilean moon observations, and may be useful ground-based context for upcoming Galilean satellite missions (JUICE and Europa Clipper).